USERS’ SATISFACTION LEVEL OF PREDIADUCATE WEBSITE AS AN EDUCATIONAL MEDIA FOR PREDIABETES PREVENTION - Jasmine Rana Sahirah; Ardesy Melizah Kurniati; Iche Andriyani Liberty; Syarif Husin; Yudhie Tanta (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Prediabetes is a condition where blood glucose is higher than normal yet to be diagnosed as diabetes. This condition is mostly not recognized by people, which worsen the condition into diabetes. Therefore, in order to prevent the worsening condition into diabetes, early detection and education about prediabetes are important. As one of the educational media, Prediaducate is expected to provide not only information but also a risks screening test, hence the prediabetes and diabetes rate can be reduced. This study is a descriptive observational with a cross-sectional design. The sample used in this study is Prediaducate’s users from August-October 2021 who met the inclusion criteria. The data was taken from a questionnaire online by using Google Forms. Later processed with STATA 15. This study concludes that most of the users’ of Prediaducate felt highly satisfied with the system quality, information quality, and interaction quality.